Targeting gut microbiota as a therapeutic target in T2DM: A review of multi-target interactions of probiotics, prebiotics, postbiotics, and synbiotics with the intestinal barrier - Keyu Chen; Han Wang; Xiaofei Yang; Cheng Tang; Guojie Hu; Zezheng Gao (Pharmacological Research)
The global epidemic of type 2 diabetes mellitus (T2DM) imposes a substantial burden on public health and healthcare expenditures, thereby driving the pursuit of cost-effective preventive and therapeutic strategies. Emerging evidence suggests a potential association between dysbiosis of gut microbiota and its metabolites with T2DM, indicating that targeted interventions aimed at modulating gut microbiota may represent a promising therapeutic approach for the management of T2DM. In this review, we concentrated on the multifaceted interactions between the gut microbiota and the intestinal barrier in the context of T2DM. We systematically summarized that the imbalance of beneficial gut microbiota and its metabolites may constitute a viable therapeutic approach for the management of T2DM. Meanwhile, the mechanisms by which gut microbiota interventions, such as probiotics, prebiotics, postbiotics, and synbiotics, synergistically improve insulin resistance in T2DM are summarized. These mechanisms include the restoration of gut microbiota structure, upregulation of intestinal epithelial cell proliferation and differentiation, enhancement of tight junction protein expression, promotion of mucin secretion by goblet cells, and the immunosuppressive functions of regulatory T cells (Treg) and M2 macrophages. Collectively, these actions contribute to the amelioration of the body's metabolic inflammatory status. Our objective is to furnish evidence that supports the clinical application of probiotics, prebiotics, and postbiotics in the management of T2DM.